Desain Pembelajaran dengan Problem Solving untuk Meningkatkan Kemampuan HOTS Materi Integral - RA Seravika Primasari; Tian Abdul Aziz; Lukman El Hakim; Flavia Aurelia Hidajat (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The instructional design with a problem-solving approach is essential for enhancing students' Higher Order Thinking Skills (HOTS) in secondary education. The aim of this research is to develop an effective and measurable learning process that can improve students' HOTS through a problem-solving approach, with a particular focus on the topic of integrals, which students often find challenging. The research method used in this study is Instructional Design Development, which integrates student needs analysis, clear learning objectives, and the application of innovative and relevant instructional strategies. This research involves a comprehensive analysis of various theories and best practices in problem-based learning, as well as evaluating its effectiveness through classroom trials. The sources of information evaluated include academic journals, textbooks, and previous research reports, providing diversity and validity of data for analysis. This analysis includes the definition of HOTS, HOTS indicators investigated, and the strategies and methods commonly used in problem-solving learning. This research aims to provide a deeper understanding of how instructional design with problem-solving can enhance students' HOTS, particularly in understanding and mastering integral material. The results of this research are expected to significantly contribute to the development of more effective and efficient learning strategies, focusing on developing students' critical and creative thinking skills in education.